Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/polym12020455
|View full text |Cite
|
Sign up to set email alerts
|

Highly-Sensitive Detection of Volatile Organic Compound Vapors by Electrospun PANI/P3TI/PMMA Fibers

Abstract: Detection of volatile organic compounds (VOCs) is one of the essential concerns for human health protection and environmental monitoring. In this study, the blending fibers using a donor-acceptor copolymer were fabricated by electrospinning technique and subsequent UV/ozone treatment. The donor-acceptor polymers were polyaniline, P3TI, and poly(methyl methacrylate) (PANI/P3TI/PMMA) fibers with a cylindrical structure and uniform morphology. VOCs were directly adsorbed by the copolymer materials assembled onto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Polyaniline/P3TI/poly(methyl methacrylate) (PANI/P3TI/PMMA) fibers were fabricated by the electrospinning technique to detect VOC vapors ( n -butanol, dimethylformamide (DMF), toluene, n -propanol and chlorobenzene). 121 The LOD for n -butanol was about 100 ppm, and the response time was less than 10 sec.…”
Section: Chemical Sensors Based On Electrospun Membranesmentioning
confidence: 99%
“…Polyaniline/P3TI/poly(methyl methacrylate) (PANI/P3TI/PMMA) fibers were fabricated by the electrospinning technique to detect VOC vapors ( n -butanol, dimethylformamide (DMF), toluene, n -propanol and chlorobenzene). 121 The LOD for n -butanol was about 100 ppm, and the response time was less than 10 sec.…”
Section: Chemical Sensors Based On Electrospun Membranesmentioning
confidence: 99%
“…Ammonia [216,259], hydrogen [217], and liquified petroleum gas [209] have been found to exchange electrons with PANI and increase the electrical resistance of PANI/ZnO composites, while the same mechanism has been found operative in the detection of electronaccepting nitroaromatics [218] such as trinitrotoluene by electron-donating polyfluorene (PFO)-based materials in composites with PS and gelatin. Volatile organic compounds such as benzene and toluene have been demonstrated to swell nanofiber composites of PEDOT:PSS/carbon nanotubes/poly(vinylpyrrolidone) [219], PANI/isoindigo-based copolymer/PMMA [220], and PFO/PMMA [221], destroying conduction pathways in these materials and increasing electrical resistance. Ethanol has been detected with a sensor made from SnO 4 /PANI/poly(hydroxy-3-butyrate), with hydrogen bonding between ethanol and amine domains, as well as dopants, being the operating mechanism [222].…”
Section: Gas and Humidity Sensorsmentioning
confidence: 99%
“…Changes in conductivity are often employed as the sensing mechanism [216][217][218][219][220][221]259,288,296], while fluorescence quenching [223,260], color changes [227], pH changes [201], and mechanical deformation/pressure changes [231,[267][268][269][270] have also been employed. Sensors have been developed for gases [216,217,[219][220][221][222]259,296], humidity [224,225,[287][288][289], explosives [218], chemical warfare agents [260,289], ions [226,227,261], and, as mentioned above, a wide variety of bioactive species such as additives, antigens, and biomolecules for detection of medical conditions. Wearable sensors have been developed to detect harmful substances, analyze bodily fluids, monitor vital signs, and record motion [201,231,[266][267][268][269][270].…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Among this series of compounds, polymer 60b, containing a terthiophene oligomeric unit, has the best characteristics. Further studies showed that a polymer composite based on the terthiophene analogue 59a, poly(methyl methacrylate), and polyaniline is capable of detecting vapors of some organic solvents (chlorobenzene, n-butanol, DMF, isopropanol, and toluene) [107]. Therein, the best sensitivity was found towards n-butanol.…”
Section: Isoindigo-based Sensor Devicesmentioning
confidence: 99%